On sums of overlapping products of independent Bernoulli random variables - Csörgö, S.; Wu, W.B. (Український математичний журнал, 2000)
We find the exact distribution of an arbitrary remainder of an infinite sum of overlapping products of a sequence of independent Bernoulli random variables.